The architecture of happiness - De Botton, Alain (Penguin Books, 2007)
What makes a house truly beautiful? Why do so many new houses appear unattractive? Why do we argue so passionately over things like sofas and artwork, and can differences in taste ever be fully resolved? To explore these questions and more, de Botton examines buildings from around the world, ranging from medieval wooden huts to modern skyscrapers. He delves into everything from sofas and cathedrals to tea sets and office buildings, drawing out a wealth of unexpected philosophical insights. The Architecture of Happiness offers an intriguing journey through the history and psychology of architecture and interior design, ultimately changing the way you perceive your own home.
Includes index.
Keywords: Architecture - Aesthetics; Interior decoration - Philosophy; Architecture and philosophy